The use of google classroom in teaching writing skills - Septina Indrayani; Ina Sukaesih (Politeknik Negeri Bali, 2022)
Writing is one of the skills that English learners must master. However, in Indonesia where English is taught as a Foreign language (EFL), it has become the most challenging skill to learn. One of the factors is the difference in the usage of subject and verb in the sentence. This paper aims to see the impact of Google Classroom usage on the learning process of writing simple sentences, specifically the accuracy of writing the Subject Verb (S-V) agreement and students’ perception of using this online tool in writing activities. A mixed-method approach is used in this study where one group pretest-posttest of writing accuracy is done for 77 Electrical Engineering students, Jakarta State Polytechnic. For qualitative data analysis, Focus Group Discussions (FGDs) are conducted. The result shows an increase in the accuracy of students’ writing accuracy specifically on the writing of S-V agreement. Furthermore, students believe that Google Classroom in the writing class is beneficial due to lesson hand-outs distribution and assignment submission efficiency.